2019
DOI: 10.1007/s11136-019-02333-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring self-report and proxy-report quality-of-life measures for people living with dementia in care homes

Abstract: Purpose There are many validated quality-of-life (QoL) measures designed for people living with dementia. However, the majority of these are completed via proxy-report, despite indications from community-based studies that consistency between proxy-reporting and self-reporting is limited. The aim of this study was to understand the relationship between self-and proxy-reporting of one generic and three disease-specific quality-of-life measures in people living with dementia in care home settings. Methods As par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…It is completed by direct care staff (mostly care aides), minimizing resident burden and cost to facilities and the system, and does not require external assessors. Although proxy reports of QoL are consistently lower than self-reports, 37 they measure the same construct as suggested by factor analyses. As noted above, DEMQOL-CH has advantages in long-term care where self-report is often impossible because of dementia severity and residents may not have a family or friend carer to provide proxy assessment.…”
Section: Demqol-chmentioning
confidence: 66%
“…It is completed by direct care staff (mostly care aides), minimizing resident burden and cost to facilities and the system, and does not require external assessors. Although proxy reports of QoL are consistently lower than self-reports, 37 they measure the same construct as suggested by factor analyses. As noted above, DEMQOL-CH has advantages in long-term care where self-report is often impossible because of dementia severity and residents may not have a family or friend carer to provide proxy assessment.…”
Section: Demqol-chmentioning
confidence: 66%
“…Conversely, we asked a sample of non-cyclists about the behavior they perceive in cyclists they have interacted with. There is some controversy on the use of proxies in different specific research areas such as healthcare, with some studies supporting their use [25][26][27] and others standing against [49]. Concerning road safety, family members and caregivers have been identified as reliable proxies [29,31,32].…”
Section: Assessing the Usefulness Of Proxies/external Raters For Cycling Behavior And Road Safetymentioning
confidence: 99%
“…When individuals are no longer able to report on their own QoL, due to cognitive impairment, family and professional ratings are used as proxies. Proxy ratings, however, often differ from patients' selfreports and from each other depending on the setting and study population [9,10] and studies comparing self-assessed QoL and proxy-rated QoL often showed that individuals rated their QoL higher than proxy raters [11][12].…”
Section: Proxy-ratings For Residents' Quality Of Lifementioning
confidence: 99%
“…The limitations of our study are consistent with those of other papers in this area. Studies to investigate Qol in residents with dementia are usually cross-sectional and characterized by small sample sizes due to an old and multimorbid population [4,7,12]. When comparing the rater assessments for the same resident, more observations would have been desirable, and longitudinal data could have provided insight into the changes in the QoL of residents and the QoL assessments over time.…”
Section: Limitations and Future Research Considerationsmentioning
confidence: 99%